(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2007)
Studies were carried out on the leaves of Cassia alata. Parahydroxy benzoic acid was isolated from the leaves of Cassia alata with the help of column and thin layer chromatography using a gradient of organic solvents with increasing polarity. The compound was characterized on the basis of UV, IR, 1H-NMR and Mass spectrometry. Bangladesh J. Sci. Ind. Res. 41(1-2), 89-92, 2006